Physicians' awareness of oral-systemic links and its association with physician-reported patient referral to dentists. - Fatimah Al-Habib; Fatimah Al Abdulbaqi; Hala Alibrahim; Yasmin Alhamdan; Muhammad Ashraf Nazir; Jehan AlHumaid (PLoS ONE, 2022)
Introduction Physicians promote oral health by screening for oral pathologies, providing emergency help, and referring patients to dentists. The literature consistently reports a robust association between periodontal disease and systemic diseases. However, it is not fully known if physicians in Saudi Arabia are aware of the oral-systemic disease links. Therefore, the study aimed to evaluate physicians' awareness of the oral-systemic disease links and their association with patients' referral to dentists and patients' access to oral care. Methods This cross-sectional study was conducted (June 2019-January 2020) on physicians working in private and public hospitals in the Eastern province of Saudi Arabia. The physicians (n = 333) responded to a paper-based self-administered and pilot-tested questionnaire which inquired about their awareness of oral-systemic disease links and patient referral to dentists. The reliability of items of oral-systemic disease links was evaluated by calculating Cronbach's alpha (0.84). Results Most participants (92.8%) agreed/strongly agreed that oral health is associated with systemic health. Half of the sample (50.8%) referred patients to dentists during the last month. Almost 80.5% believed that more patients will be referred to the dentists because of their awareness of the oral-systemic disease links and 84% believed that more patients will access oral care services if patients were aware of the oral-systemic disease links. The participants who referred patients to the dentists during the last month (P = 0.038), believed that more patients will be referred (P = 0.001), and believed that more patients will access oral care (P = 0.003) demonstrated significantly higher oral-systemic disease links awareness score. The adjusted model showed patients' referral to dentist (OR = 1.96.10, P = 0.006) and believing in more patients accessing oral care (OR = 2.05, P = 0.044) were associated with significantly increased awareness of the oral-systemic disease links. Conclusion Most physicians in the study were aware of the oral-systemic disease links. Increased awareness of the oral-systemic disease links was significantly associated with the referral of patients to dentists and belief in improved patients' access to oral care services.